KAWASAN RELIGIUS DAN PRODUKSI RUANG DI LINGKUNGAN MASJID PATHOK NEGARA PLOSOKUNING YOGYAKARTA - Rahmadi Agus Setiawan (UIN Sunan Kalijaga Yogyakarta, 2017)
Study of religion and territory (space) is a new phenomenon in recent decades along with the tendency of religious studies that change from normative to contextual approach. Plosokuning village as a religious area becomes research object that examines the relationship between religion and space. Furthermore, this research will explore how this religious region is formed and how it affects the behavior of the people in this village.This study uses a social theory known as the production of space proposed by Henri Lefebvre. In this theory, space is a social production, and always related to the social reality that surrounds it. Space never existed and manifested itself or held itself. In other words space has a historical dimension that helped shape it. The social space also influences the way of thinking and acting of society that exists in the space, as well as uses as control and domination.From the historical approach, it is found that the religious area of Plosokuning is a product of the palace (kraton Yogyakarta) that makes Plosokuning as a mutihan area (place of worship). This religious area is intended as a bastion of the spirituality of the palace and the implementation of the royal philosophy known as Kiblat Papat Lima Pancer. In this philosophy, the palace is in the middle and surrounded by a spiritual fortress in the form of four Pathok Negara Mosques, one of which is the Pathok Negara Mosque in Plosokuning.The religious area of Plosokuning, which is a palace product, has an influence on the Islamic religiosity of the Plosokuning community. This religious behavior can be proved by the emergence of cultural products, both tangible and intangible cultures. Tangible cultures are like the emergence of some boarding schools (pesantren), some musholla (small mosques), Muslim housing, and majelis ta'lim (place for Islamic studies). While intangible culture such as the emergence of Islamic art, religious rituals, as well as Islamic religious norms in society. Plosokuning as religious area continues to be inherited from generation to generation by continuing to revive the Islamic culture, both tangible and intangible culture.The study of the Plosokuning community also shows a strong relation between religious space and the behavior of the people. By the existing of the religious area, so the sacred character of religion becomes strong in the environment of Pathok Negara Mosque Plosokuning. As a sacred area, it becomes a shame (taboo) when people conduct behavior or actions that violate Islamic norms and traditions. The social function of this religion is also reinforced by giving social sanctions for people who violate the teachings of Islam. Keywords: Islam, production of space, sacred, Yogyakarta.